Early Modern Mobilities and People on the Move: An Epistemological Challenge - Ducreux, Marie-Elisabeth (Dějiny – teorie – kritika, 2020)
This essay concentrates on various aspects of mobility and motion and explores the issues of approaches and methods in history research and forms of history writing on things and people on the move in early modern times. The so-called mobility turn initiated countless new studies. Nonetheless, those publications are strikingly heterogeneous in their approaches and practices. It seems sometimes that, although we historians may be fully aware of how many categories have been eroded, how profoundly the internal historiographical clusters and boundaries have been deconstructed, we are still grappling with how best to arrange and relate structures, facts, contexts and theoretical reassessments. This essay calls for a critical historiographical self-reflection. It sets out by broaching Migration and Mobility as a social sciences and history field. Then, it briefly deals with questions of temporality and the challenges in connection to the early modern period, before developing the touchstones of the archival and methodological challenges we are facing: Sources, Traces, Archives, Facts, Levels and Scales. In addition, this paper outlines a case study and connects it to suggestions made by other scholars who have addressed the role of exile and emigration in conversion and religious affiliation. Finally, it considers how new micro-historical approaches may help historians reconcile the encounter between the global and the local when writing history.